Not a polar island: yellow fever, Spanish medical research, and the struggle for scientific and political hegemony in late nineteenth century Cuba - Francisco Javier Martínez (História, Ciências, Saúde: Manguinhos)
Abstract: This paper explores questions related to yellow fever and the political destiny of Cuba in the late nineteenth century. A forgotten therapeutic device to treat the disease invented in that period, the “polar chamber” (cámara polar), provides a useful standpoint for reconstructing the tradition of Spanish yellow fever research in Cuba, a topic largely neglected by the medical historiography. The failed history of this device can also illuminate the complex struggle for scientific hegemony between Spanish, Cuban, and US institutions and researchers. Finally, we focus on the politics of the polar chamber by analyzing how this invention intended to provide a particular solution for the complex, threefold struggle for Cuba’s political future.